KONSOLIDASI KEMANDIRIAN KELUARGA DALAM MENCEGAH STUNTING DAN MANULTRISI DI WILAYAH KERJA PUSKESMAS DESA SUMBERAGGUNG KECAMATAN PERAK KABUPATEN JOMBANG - Dwi Purwasih , Galuh; Hanifah, Laili (Proceedings of Annual Conference on Community Engagement, 2023)
Sumberagung is a village in Jombang which is the focus location for handling stunting. There were 40 stunted toddlers or 5.7%. Based on these problems, Sumberagung Village, Perak sub-district, is one of the target areas near the Perak Health Center. "fast responsive and tough together to prevent stunting and manultrition" as a form of intervention to prevent stunting and manultrition in the Perak Community Health Center working area. The aim of this service and research is to increase understanding of family independence for the prevention and reduction of stunting and manultrition rates. Perak Community Health Center held socialization on the prevention of stunting and nutrition in Sumberagung Village, Perak District, Jombang Regency, socialization on prevention in the Sumberagung Village office hall, the activity was accompanied by the village secretary, health workers, 5 pregnant women, 10 breastfeeding mothers, 5 posyandu cadres, and mothers- PKK mothers from Sumberagung Village, with a total of 15 participants. The method of implementing community service takes the form of family independence training. Implementation of activities is carried out in several stages, namely preparation, problem identification, procurement, implementation, and evaluation and participant feedback. During the pretest, 20% of participants understood family understanding, 30% of participants understood manultrition, and 70% of participants understood stunting. Meanwhile, at the posttest, 50% of participants understood family independence, 55% of participants understood parenting patterns, and 95% of participants understood stunting. So that the percentage of participants’ understanding of the material on family independence for PKK cadres in Sumberagung village, Perak Jombang sub-district shows an increase and is in good criteria.